Asymmetric aldol reactions of isatins catalyzed by phthalimido-prolinamide. Issue 21 (1st December 2015) - Kumar, Togapur Pavan; Manjula, Nemali; Katragunta, Kumar
Graphical abstract: Abstract: Enantioselective aldol reactions of isatins with acetone using phthalimido-prolinamide organocatalyst1 are described. The protocol was effective under solvent free and additive free reaction conditions with 20 mol % of1 leading to the desired aldol products in good yields and with good enantioselectivities. Abstract : ( S )-3-Hydroxy-3-(2-oxopropyl)indolin-2-one: C11 H11 NO3 [ α ]D 20 = −24.1 ( c 1, CH3 OH) Source of chirality: asymmetric aldol reaction Absolute configuration: ( S )